ANALISIS PERBANDINGAN PELAPORAN DAN PENGUNGKAPAN ASET BIOLOGIS SEBELUM DAN SETELAH PENERAPAN IAS (INTERNATIONAL ACCOUNTING STANDARD) 41 PADA PT. ASTRA AGRO LESTARI, TBK - Putri, Sulistyorini Rafika (Jurnal Akuntansi AKUNESA, 2014)
Agricultural sector is very interesting to be discussed related to the enforcementof the use of IAS 41 as the basis for the accounting treatment company that has aunique characteristic asset that biological assets. Based on IAS 41 biologicalasset is a living animal or pant. This property is unique because it always changesor biological transformation consisting of growth, degeneration, production andprocreation. Financial statements and disclousure which is the ultimate goal forall transactions, will be amended when the presentation, due to the application ofIAS 41 assets biological will be measured at fair value, as previously allplantation companies use historical cost as a measurement method. Thediscussion of PT. Astra Agro Lestari, Tbk was found that the plantation firms whohave gone public is not yet fully implemented IAS 41 only some of the provisionsare already run by PT. Astra Agro Lestari Tbk.Keywords: Biological Asset, IAS 41, Fair Value, Financial Statements,Disclousure